2013
DOI: 10.1371/journal.pone.0061491
|View full text |Cite
|
Sign up to set email alerts
|

TNFα Modulates Fibroblast Growth Factor Receptor 2 Gene Expression through the pRB/E2F1 Pathway: Identification of a Non-Canonical E2F Binding Motif

Abstract: Interactions between epithelium and mesenchyme during wound healing are not fully understood, but Fibroblast Growth Factors (FGFs) and their receptors FGFRs are recognized as key elements. FGFR2 gene encodes for two splicing transcript variants, FGFR2-IIIb or Keratinocyte Growth Factor Receptor (KGFR) and FGFR2-IIIc, which differ for tissue localization and ligand specificity. Proinflammatory cytokines play an essential role in the regulation of epithelial-mesenchymal interactions, and have been indicated to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Total RNA from biopsies or cell cultures was extracted using TRIzol reagent (Invitrogen by Life Technologies, Carlsbad, CA, USA) following the manufacturer's instructions. Quantitative real‐time PCR (qRT‐PCR) was performed as previously described (D'Amici et al., ). Briefly, cDNA obtained were used for amplification of αSMA and vimentin using the appropriate TaqMan gene expression assay kits (Applied Biosystems by Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA from biopsies or cell cultures was extracted using TRIzol reagent (Invitrogen by Life Technologies, Carlsbad, CA, USA) following the manufacturer's instructions. Quantitative real‐time PCR (qRT‐PCR) was performed as previously described (D'Amici et al., ). Briefly, cDNA obtained were used for amplification of αSMA and vimentin using the appropriate TaqMan gene expression assay kits (Applied Biosystems by Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were lysed in RIPA buffer and processed for Western blot analysis as previously described (D'Amici et al., ). Membranes were incubated overnight at 4°C with the following antibodies: anti‐Vimentin (1:500 dilution; Dako), anti‐αSMA (1:1,000 dilution; Sigma), Col1a1 (1:3,000 dilution; Merk Millipore), LC‐3 (1:2,000 dilution; Sigma), p62 (1:1,000 dilution; BD Biosciences), p‐mTOR (1:1,000 dilution; Cell Signaling Technology), p‐AKT (1:1,000 dilution; Cell Signaling Technology), followed by the appropriate horseradish peroxidase (HRP)‐conjugated secondary antibody (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is consistent with ATIICs being less sensitive to KGF. Similarly, Marchese et al demonstrated that KGFR gene and protein expression could be modulated by proinflammatory cytokines and oxidative stress [39,40,41], and excessive oxidative stress induced by UVB could result in the internalization of KGFR after temporary UVB exposure [40]. Down-regulation was observed 6 h to 24 h after UVB exposure [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cells were lysed with RIPA buffer purchased by Sigma-Aldrich (St. Louis, MO, USA) and total proteins were run using Invitrogen Bolt Bis-Tris 4-12% Plus gels precast polyacrylamide gels [43]. Proteins were then transferred using the iBlot ® Transfer Stacks in nitrocellulose membranes through the fast iBlot®Dry Blotting System (ThermoFisher Scientific, Foster City, CA, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%